Psychospołeczne skutki wdrażania zmian na przykładzie implementacji zintegrowanego systemu informatycznego - Molek-Winiarska, Dorota (Psychosociological effects of improvements i.e. the implementation of computing systems in organizations, 2006)
This article presents results of the research devoted to psychosociological effects of changes in organization. The main aim is to analyse those psychosociological phenomena which occur in the process of the implementation of computing systems in organizations. The research takes into account such behaviours as: stress, workload, resistance to changes as negative factors and the ability to learn fast and participation in managerial decisions as positive ones. The procedure of the research and implications for practitioners are shown. Moreover, it is described how to reduce or eliminate stress, workload and resistance to changes during the process of implementation. The results of the research could be the basis to create the procedure of effective implementation, to reduce negative behaviours and to strengthen positive ones.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 49-67